Achieving a useful and person‐centred diabetes consultation is a shared responsibility between diabetologists and people with diabetes: a qualitative study of perspectives from people with type 1 diabetes. Issue 6 (23rd September 2020) - Schultz, A. A.; Wad, J. L.; Willaing, I.; Nørgaard, K.; Persson, F.; Joensen, L. E.
Abstract: Aims: To explore perceptions of useful routine consultations with diabetologists from the perspective of adults with type 1 diabetes, including preferences for discussing psychosocial issues. Methods: We conducted semi‐structured interviews in 2018/2019 with 33 people with type 1 diabetes (age 22–75 years, 20 men and 13 women, median diabetes duration 25 years) recruited from two diabetes clinics in the capital region of Denmark. Interviews were audio recorded, transcribed verbatim and analysed using thematic text condensation. Results: Achieving a useful consultation was perceived as a shared responsibility between people with diabetes and diabetologists. Participants' perspectives of what constitutes a useful consultation and expectations for both consultation and diabetologist varied in relation to perceptions of (1) the interaction between the person with diabetes and diabetologist, including being prepared, being honest, experiencing good rapport and preferring a partnership with the diabetologist or 'keeping it clinical' and (2) the diabetologist's approach to diabetes care, including providing up‐to‐date knowledge and listening and showing understanding. Conclusions: Both content and style of diabetes consultations need to be adapted to the individual person with type 1 diabetes. People with diabetes have an important role in expressing their needs and preferences related to both content and style. Diabetologists need to be aware of and attentive to the many individual needs and expectations among people with diabetes, including the desire and need to discuss psychosocial issues. Dialogue tools for preparation and in consultations may enable people with diabetes to voice their needs and expectations and diabetologists to juggle these diversities.